Peran Agama Kristen dalam Hubungan Internasional - Farasi, Neni Gusti Endang; Nainggolan, Manahan Zulkifli; Sijabat, Ribka Zulkifli (Universitas Komputer Indonesia, 2023)
Although religion has never been absent from international relations, since the Iranian Revolution, the end of the Cold War, and the events of 9/11, the international community has renewed interest. Questions centered on the role of religion in peace and conflict, the compatibility of religious laws and norms with different government systems, and the influence of religious actors on various issues. Reliance on Enlightenment assumptions, which associated